The Observable Students’ Divergent Approach as Experienced in a Seminar on Language Teaching Class - Didik Rinan Sumekto (Soegijapranata Catholic University, 2018)
This study aims at observing the undergraduate students’ divergent approach experience toward their language teaching seminar’ presentation and discussion. Ninety-one students (n=91) of English education department participated as the respondents. Data collection used a random sampling, whereas data analysis was examined through the descriptive statistics, simple correlation and two-tailed regression analysis with the significance level of .05. The divergent approach was found as a moderate category. The findings showed that M=17.44; SD=2.829 for learning control and objectives, M=19.70; SD=3.638 for language awareness, and M=11.97; SD=2.095 for students’ interaction with the significance level of F=62.564; R²=.683; and p.00. The partial linearity analysis of learning control and objectives showed that t=3.645; p=.000, language awareness was t=2.648; p=.010, and students interaction was t=4.341; p=.000. These three predictors contributed a positive and significant influence toward the divergent approach. In further, a step-wise equivalence was applied to accommodate the two-tailed regression analysis, where its equivalence was Y=1.014+.381X1+.253X2+.660X3